Beauty-is-good, ugly-is-risky - Castagna, Ana Carina (2021)
Castagna, A. C., Pinto, D. C., Mattila, A., & Barcellos, M. D. D. (2021). Beauty-is-good, ugly-is-risky: Food aesthetics bias and construal level. Journal of Business Research, 135, 633-643. https://doi.org/10.1016/j.jbusres.2021.06.063 ---%ABS3%